An empirical examination of the moderating role of age and gender in consumer mobile banking use: a cross-national, quantitative study. Issue 4 (24th August 2020) - Merhi, Mohamad; Hone, Kate; Tarhini, Ali; Ameen, Nisreen
Abstract : Purpose: Despite the benefits of mobile banking services in an increasingly digitised world, adoption rates remain unsatisfactory. The present cross-national study examines age- and gender-dependent variations of consumer intentions and use of mobile banking services. Design/methodology/approach: The study analyses consumer mobile banking use by integrating factors such as with trust, security and privacy and it examines the effects of these factors among two demographic factors including age and gender. 897 Lebanese and British mobile banking users completed a survey. Data was analysed by partial least squares-structural equations modelling. Findings: Consumer behavioural intention was significantly moderated by age through its relationship with facilitating conditions and trust among Lebanese respondents, and performance expectancy, effort expectancy, hedonic motivation, price value and habit among their British counterparts. As for gender, a significant moderating effect was evidenced in the Lebanese, but not the British sample, on the level of performance expectancy, effort expectancy, facilitating conditions, price value and perceived security. Originality/value: The findings provide evidence of the applicability of the new factors proposed in this research. The reflection of the influence of these demographic factors in a cross-national context provides insights into mobile banking adoption variation between different countries.